2006
DOI: 10.2320/matertrans.47.1214
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and Thermal Property of MgB<SUB>2</SUB>/Aluminum Matrix Composite Materials Fabricated by 3-Dimensional Penetration Casting Method

Abstract: Superconductive MgB 2 /Al composite material with low and high volume fractions of particles were fabricated by our special pre-packing technique and 3-dimensional penetration casting method. The composite material showed homogeneous distribution of MgB 2 particles in the Al-matrix with neither any aggregation of particles nor defects such as cracks or cavities. The critical temperature of superconducting transition (T C ) was determined by electrical resistivity and magnetization to be about 37-39 K. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…No data on wetting properties of AlB 2 , CaB 6 , and MgB 2 with liquid aluminum and its alloys have been published so far. For MgB 2 , an investigation has been made concerning superconductivity of aluminum infiltrated MgB 2 , but no information about wetting was given . The same applies with regard to AlB 2 or CaB 6 except a few reports on the formation of AlB 2 and CaB 6 in aluminum melt and on the application of particulate CaB 6 reinforced aluminum matrix composites…”
Section: The Properties Of the Ceramic Substrates Used For The Wettabmentioning
confidence: 99%
“…No data on wetting properties of AlB 2 , CaB 6 , and MgB 2 with liquid aluminum and its alloys have been published so far. For MgB 2 , an investigation has been made concerning superconductivity of aluminum infiltrated MgB 2 , but no information about wetting was given . The same applies with regard to AlB 2 or CaB 6 except a few reports on the formation of AlB 2 and CaB 6 in aluminum melt and on the application of particulate CaB 6 reinforced aluminum matrix composites…”
Section: The Properties Of the Ceramic Substrates Used For The Wettabmentioning
confidence: 99%
“…The details of sample preparation have been given elsewhere. 19) The powders were firstly ground in an agate mortar; secondly a preform of compacted MgB 2 powders of about 30 mm in diameter and 42 mm in length was prepared; the preform was located in a bottom of a steel mold and a host material of magnesium (or magnesium alloy) was placed on the preform; the mold was heat up to an appropriate temperature (the casting temperatures are given in Table 1 for all the samples); finally when the host material started to melt, a graphite disc from the top of the mold pressed to impregnate MgB 2 powders with the host material. The pressure was about 14 MPa.…”
Section: Methodsmentioning
confidence: 99%
“…A low temperature casting is a great advantage of SS-3DPC compared the PIT method, in which high temperature heat treatments easily introduced large voids in MgB 2 grains. Our previous work on MgB 2 /Al composite material demonstrated that the superconducting transition temperature (T c ) was observed at 38 K on the resistivity, a superconducting volume fraction estimated from magnetization was about 50%, 19) and further a superconducting wire of MgB 2 /Al of 1 mm diameter was extruded. 20) It has been known, however, that addition of aluminum to MgB 2 results in the loss of superconductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8) The authors also have fabricated and reported composite materials of aluminum that exhibit, for example, photocatalytic properties of TiO 2 and superconducting properties of MgB 2 without compromising the properties of the functional composite particles by suppressing the reaction between the composite particles and aluminum matrix. 9,10) CeNFs are carbonized at around 200400°C. 3,11,12) Therefore, it is difficult to fabricate CeNF near the melting point of aluminum because CeNF is completely carbonized by the fabrication method using molten aluminum, which the authors have conventionally used.…”
Section: Introductionmentioning
confidence: 99%